1992
DOI: 10.1103/physrevlett.68.2488
|View full text |Cite
|
Sign up to set email alerts
|

Shear displacement of the K(110) surface

Abstract: A low-energy electron diffraction analysis of the clean K(l 10) surface has been performed at 25 K, providing a quantitative structural determination of a clean alkali-metal surface. The K(110) surface exhibits a novel surface phase consisting of a lateral shear displacement between the first two surface planes while preserving their two-dimensional periodicity. The atomistic description of this surface structure is related to that of the bulk martensitic phase transitions of the alkali metals.General interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…It is well known (see, for instance, Refs. [27,28]) that it is very difficult to distinguish between static and dynamical displacements in LEED analysis, and we believe that Table I carries strong indications that in the actual surface some degree of structural disorder is present, which has erroneously been attributed to dynamical effects. Deviations from clean and flat morphology would certainly affect the apparent rms displacements, the layer relaxations, and their temperature dependence in LEED analysis of "nominally ideal" surfaces.…”
Section: Istituto Nazionale DI Fisica Della Materia (Infm) and Scuolamentioning
confidence: 90%
“…It is well known (see, for instance, Refs. [27,28]) that it is very difficult to distinguish between static and dynamical displacements in LEED analysis, and we believe that Table I carries strong indications that in the actual surface some degree of structural disorder is present, which has erroneously been attributed to dynamical effects. Deviations from clean and flat morphology would certainly affect the apparent rms displacements, the layer relaxations, and their temperature dependence in LEED analysis of "nominally ideal" surfaces.…”
Section: Istituto Nazionale DI Fisica Della Materia (Infm) and Scuolamentioning
confidence: 90%
“…Low energy electron diffraction experiments of the {110} surface revealed the signature of large shears of the surface layer relative the bulk. Electronic structure calculations suggested that force constants governing the shear of the surface layers were so small that zero point motion alone could account for the experimental observations 15,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Such an in situ growth of alkali-metal single crystals provides a unique opportunity to prepare well ordered and clean surfaces of these fundamentally interesting metals. 6,7 More recently, helium atom scattering ͑HAS͒ was applied to investigate the growth of Na films deposited on Cu͑001͒ ͑Ref. 8͒ and of Na, Rb, and Cs films on a graphite surface.…”
Section: Introductionmentioning
confidence: 99%